(untitled) (World of finance, 2021)
Introduction. In the current conditions of global transformations, the impact of pandemic challenges and threats, the level of digitalization of public administration in general and the level of information support of fiscal authorities in particular play a key role. The use of effective technologies of informatization of the customs authorities of the state creates favorable conditions for the movement of goods across the state border by simplifying, accelerating and improving the procedures of customs clearance and customs control. Today there is an urgent need to unify the national legal framework in the field of customs to international standards, improve the technological, institutional and infrastructural direction of reforming the customs authorities of the state and to intensifyty the processes of digitalization in Ukrainian customs policy. The purpose of the article is to study the specifics of the activities and tasks of reforming the information support in the state customs authorities, to outline priorities and obstacles to improving the efficiency of customs institutions in Ukraine and in the economic avant-garde countries on the context of digital strategy of society. Methods. In studying the features of information support of customs in Ukraine and the level of informatization of customs authorities in particular, a set of general scientific and special research methods was used, covering: analysis and synthesis, generalization and statistical. Results. As a result of the study of information support of the customs of Ukraine, the basis of its implementation is systematized, the transformational features of information support of the customs authorities of the state are analyzed. The experience of informatization of the customs space of economically developed countries in the conditions of digitalization of the economy is analyzed. Modern information systems of the customs authorities of Ukraine and the peculiarities of their functioning are outlined. The advantages and obstacles of accession of the customs authorities of the state to the Convention on the procedure of joint transit are detailed. The problematic aspects that prevent the increase of efficiency of information support in the LCA of Ukraine are determined. Prospects. Further research is planned to focus on assessing the level of efficiency of the customs information system in Ukraine and developed countries, analysis of security, fiscal and economic effects of digital transformations of customs procedures, areas of implementation of best practices of informatization of customs institutions.